2010
DOI: 10.1002/jat.1609
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology and human health: risks and benefits

Abstract: Nanotechnology is expected to be promising in many fields of medical applications, mainly in cancer treatment. While a large number of very attractive exploitations open up for the clinics, regulatory agencies are very careful in admitting new nanomaterials for human use because of their potential toxicity. The very active research on new nanomaterials that are potentially useful in medicine has not been counterbalanced by an adequate knowledge of their pharmacokinetics and toxicity. The different nanocarriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(57 citation statements)
references
References 157 publications
(141 reference statements)
0
55
0
2
Order By: Relevance
“…23,24 These potential routes of NP exposure are summarized graphically in Figure 1. Importantly, the route of exposure ultimately determines which body system or specific tissues the NPs interact with which in turn determines the effects of NP exposure such as toxicity 25,26 or alterations in physiological function. 27 The effects of NP exposure can be divided into primary and secondary categories (Figure 1), depending upon the extent of exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 These potential routes of NP exposure are summarized graphically in Figure 1. Importantly, the route of exposure ultimately determines which body system or specific tissues the NPs interact with which in turn determines the effects of NP exposure such as toxicity 25,26 or alterations in physiological function. 27 The effects of NP exposure can be divided into primary and secondary categories (Figure 1), depending upon the extent of exposure.…”
mentioning
confidence: 99%
“…22,26,102,103 Although the effects of WC-Co particles have been established in multiple cell lines of varying origin, most of these studies used mono-culture systems in their examination of WC-Co particle toxicity, which may not provide an accurate assessment of what happens during/after WC-Co exposure since the local environment of the lung is highly dynamic and contains more than a single cell type. In a recent study, 87 the inflammatory response toward nano-WC-Co particles in macrophages and the toxicity of WC-Co have been examined using a co-culture model of lung epithelial cells and macrophages to more closely represent the dynamic tissue environment of the lung.…”
mentioning
confidence: 99%
“…[1][2][3] However, safety concerns restrict the number of suitable materials, and further research is required to demonstrate the absence of risks as well as the real benefits to human health. 34,35 Biodegradable and biocompatible polyesters are an interesting class of substrates because many of them, including poly(l-lactide) and its copolymers, have regulatory approval for some applications in humans, being degraded in the body into endogenous products by non-enzymatic hydrolysis. 36,37 In this paper, we compared the properties of pristine PLLA sc and APLLA sc and showed that both adsorbed large amounts of HPV16-E7 protein.…”
Section: Discussionmentioning
confidence: 99%
“…As for therapeutic exploitation of Nanothecnology, the focus of this chapter, one of the main advances in this area is the use of nanoproducts as carriers of chemotherapy agents, producing nanodrugs. These carriers may be of different origins, but one the most used ones for drug delivery are the lipid nanocarries, which include liposomes and multilamellar, multivesicular liposomes, nanostructured lipid carries and solid lipids (Cattaneo et al, 2010). Yet, the carriers themselves may have some modifications to avoid the immune system, enhancing the drug availability to the organism.…”
Section: Nanothecnology and The Development Of Novel Drugsmentioning
confidence: 99%